Analisis Sumber Daya Dalam Program Pernikahan Gratis di Kantor Urusan Agama Kecamatan Pakal Kota Surabaya - Endik Hidayat (Jurnal Penelitian Administrasi Publik, 2020)
One of the duties of the Office of Religious Affairs (KUA) refers to the Regulation of the Minister of Religion No. 2 of 2019 is to register marriage. The registration process is free if the marriage is carried out at the KUA office. This article answers the inhibiting factors from the resource aspect of the free marriage program at KUA Pakal District. Because based on marriage data from 2019 to 2020 people prefer to carry out marriages outside the KUA office. This article uses a qualitative method with a descriptive approach in the case of KUA Pakal District. Data collection techniques were carried out through observation, in-depth interviews with KUA employees, and secondary data in the form of KUA Pakal profiles and KUA documentation. This article finds the obstacles to free marriage services at the KUA due to the lack of resources for implementing the program. The resources are viewed from four main components, namely: (1) human resource problems related to the lack of number of employees. (2) limited budget resources for renovation of buildings in poor condition. (3) inadequate equipment resources in providing convenient services. (4) information resources and authority. Keywords: Resource; Policy Implementation; KUA